National Survey of the Family and Domestic Violence and Sexual Assault Workforces, Service Leaders Survey, 2017 - Cortis, Natasha (ADA Dataverse, 2020)
The National Survey of the Family and Domestic Violence and Sexual Assault Workforces, 2017 study involved two surveys, the design and interpretation of which was informed by stakeholder consultations. Two survey instruments were used: (1) a survey of service leaders, which was distributed for completion by a senior staff member responsible for workforce management or workforce development in their service; and (2) a survey of workers. This is the survey of service leaders, which captured experiences of leaders in services used by people affected by violence. It captured their characteristics, and their perspectives on various areas of practice. Questions include levels of contact with people affected by violence in their organisations, their experience and qualifications, employment arrangements, competence in recognising and responding to violence, training and support, supervision, and job quality.